Anfis sobre Platón (fr. 13 K.-A.) - López Cruces, Juan Luis (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2008)
In this study of Amphis fr. 13 K.-A., the author (1) examines the meaning of Dexidemides the title of the comedy, and (2) explores the possible developments of the comparison of Plato with a snail. (3) He proposes that the model Amphis is parodying is Soph. fr. 945 Radt. Finally, (4) he studies the elements of the Sophoclean verses which, in the light of the parody, could be reinterpreted as jibes directed against Plato, and (5) tentatively suggests that, thanks to Amphis’ parody, Diogenes the Cynic may have seen the anti-Platonic potential of the Sophoclean verses and reused them against Plato in one of his tragedies; this would explain why they have been attributed to Diogenes in some strands of the gnomological tradition.
Keywords: Amphis; Plato; Diogenes Laertius; Sophocles; Diogenes the Cynic; Aristophanes; Euripides; Epictetus; Gnomological tradition; Snail; Swan